How villages contribute to their local air quality – The influence of traffic- and biomass combustion-related emissions assessed by mobile mappings of PM and its components. (15th October 2021) - Fachinger, Friederike; Drewnick, Frank; Borrmann, Stephan
Abstract: Mobile mapping experiments were performed in two villages (~400 and ~2500 inhabitants, respectively) in France and Germany in both summer and winter in order to assess the pollutant distribution of several particulate matter (PM) related pollutants (particle number concentration, PM1, PM2.5, PM10 ; PM1 chemical composition, including inorganic and organic species, black carbon, and polyaromatic hydrocarbons) as well as CO2 . Two dominating local emission contributions were found: traffic contributed to organic aerosol (OA), CO2, particle number concentration, PM1, black carbon, and polyaromatic hydrocarbons, whereas significant primary emission contributions from biomass combustion were found for OA, PM1, sulfate, nitrate, and chloride. In order to quantify the respective contributions from these two sources, emission ratios of pollutants to OA were determined. By these means, contributions of traffic and biomass combustion to total PM1 could be disentangled, and it was found that even though traffic-related PM1 was higher in winter than in summer, the majority of additional locally emitted PM1 in winter was due to emissions from biomass combustion. Non-refractory inorganic components were found to make up ~5% of total PM1 primary emissions from biomass combustion. While strongly enhanced pollutant concentrations were observed under inversion conditions, the relative contributions of local emissions to the locally measured pollutant burden seemed not to be altered under such conditions. Graphical abstract: Image 1 Highlights: Mobile mapping experiments give spatially highly resolved pollutant distributions. Emission ratios of key pollutants from real-world traffic and biomass combustion. For PM1 from biomass combustion, ~5 wt% originate from non-refractory inorganics. Even in a village of only ~2500 inhabitants, ~50% of PM air pollution home-made. Inversion conditions do not affect relative local contribution to total PM burden.